Listening and observing - Winzurk, Judith D. (South-Western Educational Pub.,Career Solutions Training Group, 2000)
Listening is a form of communicating, Powerful Listening, Barriers to Listening, Listening to Non-verbal communications, Listening filters, Become a better listener...